2004
DOI: 10.3402/meo.v9i.4353
|View full text |Cite
|
Sign up to set email alerts
|

MD/MBA Students: An Analysis of Medical Student Career Choice

Abstract: Students entering these programs do so for a variety of reasons and plan diverse careers. These findings can provide guidance for program development and recruitment for dual degree medical education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 6 publications
2
19
2
1
Order By: Relevance
“…This finding is inconsistent with Sherrill's (2004) finding that individuals indicated that income prospects were the main motives in career decision making of participants in their study.…”
Section: Securitycontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is inconsistent with Sherrill's (2004) finding that individuals indicated that income prospects were the main motives in career decision making of participants in their study.…”
Section: Securitycontrasting
confidence: 99%
“…This finding is inconsistent with Sherrill's (2004) finding that prestige was one of the most important reasons for choosing a career. This low rating may suggest that most of the participants in the present study did not regard psychology as having the social status of the health professions.…”
Section: Prestige and Respectcontrasting
confidence: 78%
“…According to Vaidya et al, the categories of variables include sociodemographic factors, personal experiences, characteristics of speciality, and medical student personality traits (Vaidya et al, 2004). Regarding Sherrill, unique environment of the medical school has a major impact on students' perceptions of the practice of medicine and their career decisions (Sherrill, 2004). Medical school often represents the students' first contact with medical culture, the shared understanding and perspective of the medical profession.…”
Section: Discussionmentioning
confidence: 99%
“…Medical school often represents the students' first contact with medical culture, the shared understanding and perspective of the medical profession. The future perspective of health care is changing in a rapid manner (Sherrill, 2004). Important decision such as choice of medical career is life changing, complex, stressful and is influenced by a variety of determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Although linear algebra is a classic technique, there have been interesting new uses for eigenvectors and their associated eigenvalues. Even the career choices of medical students [8] have been subjected to this kind of examination. In his wide raging analysis of co-citations of 50 leading medical informaticians [9], Andrews includes eigenvectors to capture the variability in his data.…”
mentioning
confidence: 99%